LEGAL FRAMEWORK OF DOMESTIC VIOLENCE AMONG WOMEN - Singh, Shailender; Ali, Haider; Sinha, Nimisha (International Journal of Psychosocial Rehabilitation, 2020)
One of the most pressing social issues of our time is violence against women, and specifically domestic violence against women. A violent act against a woman, whether in public or in private, is defined by the United Nations as "any act of gender-based violence that results or is likely to result in physical or sexual harm or mental suffering for women, including threats of such acts, coercion, or arbitrary deprivation of liberties" (VAW). Discrimination and oppression against women is one of the most common abuses of human rights in the world today. An intimate partner or other members of the family might commit domestic violence against a woman, which is known as domestic violence against women (DVAW). Domestic violence can involve rape, abuse, and even murder perpetrated by a romantic relationship’s intimate partner. Forcible pregnancies, abortions, and sterilizations are further forms of violence against women, as are detrimental traditional practices such as dowry abuse and honour killings. At home, where they should feel safe and protected, women are at risk.